Co-expression of Vascular Endothelial Growth Factor and Interleukin-1 Receptor Antagonist for Improved Human Islet Survival and Function - Jia, Xiangxu (2007)
Ex vivo gene therapy approaches can improve the outcome of islet transplantation for treating type I diabetes. We have recently shown improvement in islet survival and function following ex vivo infection of islets with a mixture of adenoviral vectors encoding human vascular endothelial growth factor (Adv-hVEGF) and human interleukin-1 receptor antagonist (Adv-hIL-1Ra). In this study, we constructed a bicistronic vector encoding these two genes (phVEGF-hIL-1Ra) by cloning hIL-1Ra under the cytomegalovirus (CMV) promoter and hVEGF under the elongation factor-1α (EF-1 α) promoter in pBudCE4.1 vector. There was dose and time dependent expression of hVEGF and hIL-1Ra at both mRNA and protein levels after transfection with human islets. Transfected islets were viable, as evidenced by insulin release upon glucose challenge. Co-expression of hVEGF and hIL-1Ra suppressed nitric oxide production, total caspases, apoptosis and necrosis in the presence of inflammatory cytokine cocktail consisting of IL-1β, TNFα and IFNγ. In conclusion, our results indicated that co-expression of growth factor and antiapoptic genes can improve islet survival and function.